2014
DOI: 10.1103/physrevb.89.045317
|View full text |Cite
|
Sign up to set email alerts
|

Spin noise in the anisotropic central spin model

Abstract: Spin-noise measurements can serve as direct probe for the microscopic decoherence mechanism of an electronic spin in semiconductor quantum dots (QD). We have calculated the spin-noise spectrum in the anisotropic central spin model using a Chebyshev expansion technique which exactly accounts for the dynamics up to an arbitrary long but fixed time in a finite size system. In the isotropic case, describing QD charge with a single electron, the short-time dynamics is in good agreement with a quasi-static approxima… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
124
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(132 citation statements)
references
References 50 publications
8
124
0
Order By: Relevance
“…In particular, it has been suggested that the nuclear Zeeman effect, absent in our model, leads to a significant decrease in the mode-locking rate [53,57]. Further interactions that affect the nuclear dynamics are the quadrupolar interaction of the nuclei (in case they are considered as spin-3 2 particles) [39][40][41][42], the dipoledipole interaction between nuclei [43], and anisotropy of the dipolar hyperfine interaction or of the g factors (in case of a hole central spin rather than an electron) [40,47,[61][62][63][64][65]. The present framework of perturbation theory could be extended with these additional interactions with relatively small effort.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it has been suggested that the nuclear Zeeman effect, absent in our model, leads to a significant decrease in the mode-locking rate [53,57]. Further interactions that affect the nuclear dynamics are the quadrupolar interaction of the nuclei (in case they are considered as spin-3 2 particles) [39][40][41][42], the dipoledipole interaction between nuclei [43], and anisotropy of the dipolar hyperfine interaction or of the g factors (in case of a hole central spin rather than an electron) [40,47,[61][62][63][64][65]. The present framework of perturbation theory could be extended with these additional interactions with relatively small effort.…”
Section: Discussionmentioning
confidence: 99%
“…For the last step, one could remain within a fully quantum mechanical description [10,17] but is limited to a relative small number of nuclear spins [17,19], or to short-time dynamics [10] using a TD-DMRG approach [22]. Alternatively, one can map the dynamics onto a set of classical equations of motion [5,12,23] which shows remarkably good agreement with the full quantum mechanical treatment [10] but is easily extendable to a large number of spins.…”
Section: B Methodsmentioning
confidence: 99%
“…We are either restricted to small nuclear system sizes [17,19] or we employ the frozen nuclear approximation [5], and arrive at independent Lindblad equationṡ…”
Section: Lindblad Approachmentioning
confidence: 99%
See 2 more Smart Citations